Endothelial-Initiated Crosstalk Regulates Dental Pulp Stem Cell Self-Renewal. (August 2020) - Oh, M.; Zhang, Z.; Mantesso, A.; Oklejas, A.E.; Nör, J.E.
Interactions with the microenvironment modulate the fate of stem cells in perivascular niches in tissues (e.g., bone) and organs (e.g., liver). However, the functional relevance of the molecular crosstalk between endothelial cells and stem cells within the perivascular niche in dental pulps is unclear. Here, we tested the hypothesis that endothelial cell–initiated signaling is necessary to maintain self-renewal of dental pulp stem cells. Confocal microscopy showed that ALDH1 high and Bmi-1 high stem cells are preferentially localized in close proximity to blood vessels in physiological human dental pulps. Secondary orosphere assays revealed that endothelial cell–derived factors (e.g., interleukin-6 [IL-6]) promote self-renewal of dental pulp stem cells cultured in low-attachment conditions. Mechanistic studies demonstrated that endothelial cell–derived IL-6 activates IL-6R (IL-6 Receptor) and signal transducer and activator of transcription 3 (STAT3) signaling and induces expression of Bmi-1 (master regulator of stem cell self-renewal) in dental pulp stem cells. Transplantation of dental pulp stem cells stably transduced with small hairpin RNA (shRNA)–STAT3 into immunodeficient mice revealed a decrease in the number of blood vessels surrounded by ALDH1 high or Bmi-1 high cells (perivascular niches) compared to tissues formed upon transplantation of vector control stem cells. And finally, in vitro capillary sprouting assays revealed that inhibition of IL-6 or STAT3 signaling decreases the vasculogenic potential of dental pulp stem cells. Collectively, these data demonstrate that endothelial cell–derived IL-6 enhances the self-renewal of dental pulp stem cells via STAT3 signaling and induction of Bmi-1. These data suggest that a crosstalk between endothelial cells and stem cells within the perivascular niche is required for the maintenance of stem cell pools in dental pulps.